Borylation and rearrangement of alkynyloxiranes: a stereospecific route to substituted α-enynes - Fuentespina, Ruben Pomar; Garcia de la Cruz, José Angel; Durin, Gabriel; Mamane, Victor; Weibel, Jean-Marc; Pale, Patrick (Beilstein Journal of Organic Chemistry, 2019)
1,3-Enynes are important building blocks in organic synthesis and also constitute the key motif in various bioactive natural products and functional materials. However, synthetic approaches to stereodefined substituted 1,3-enynes remain a challenge, as they are limited to Wittig and cross-coupling reactions. Herein, stereodefined 1,3-enynes, including tetrasubstituted ones, were straightforwardly synthesized from cis or trans-alkynylated oxiranes in good to excellent yields by a one-pot cascade process. The procedure relies on oxirane deprotonation, borylation and a stereospecific rearrangement of the so-formed alkynyloxiranyl borates. This stereospecific process overall transfers the cis or trans-stereochemistry of the starting alkynyloxiranes to the resulting 1,3-enynes.
Keywords: boron; enyne; lithium; oxirane; rearrangement